Primary education during the “Liberating Revolution”: the case of the province of Buenos Aires (1955-1958) (Quinto Sol, 2014)
The purpose of this paper is to analyze primary education policy during the administration of the self-proclaimed “Liberating Revolution”. The few studies that have examined this issue state that the Liberating Revolution government erased the traces that Peronism had left in the education system. Our interest is to review this process. To do this, we analyze the conflicts within the government, the institutional design of education governance and internal organization of schools. We ask whether despite the ideological and political ruptures, it is possible to find elements ofcontinuity with the previous period. Our empirical observation area isthe province of Buenos Aires.
Keywords: education; politics; Liberating Revolution; province of Buenos Aires